Games-based learning advancements for multi-sensory human computer interfaces techniques and effective practices - Connolly, Thomas, 1957-; Stansfield, Mark, 1963-; Boyle, Liz (Information Science Reference, 2009)
"This book provides an extensive treatment of the field of games-based learning, providing a presentation of what we know about the subject, where the key challenges lie, and some of the approaches to addressing these key challenges"--Provided by publisher.